A influência da insegurança alimentar na ansiedade e qualidade de vida na em mulheres - Trajano, Flávia Maiele Pedroza (2020)
INTRODUCTION: Food insecurity has a major impact on public health in general. In the female population, it is observed that this problem gains a much greater magnitude, considering the presented particularities by this population, whether they are biological, cultural and/or social. The literature emphasizes that several factors can influence the food security of the population, among them we can mention the indicators of Mental Health and Quality of Life. OBJECTIVE: To observe the influence of anxiety levels and quality of life on food insecurity in pregnant and non-pregnant women. METHODOLOGY: This is a prospective cohort study that will be recruited into two groups: the first from families of non pregnant women and the second from pregnant women. The population of the study are families residing in the city of João Pessoa and registered in the Basic Family Health Units. The women were responsible for answering the instruments applied by the interviewers. For collection, family identification questionnaires were applied; Brazilian Food Insecurity Scale (EBIA); State-Trait Anxiety Inventory (STAI) and the World Health Organization's Quality of Life Assessment Instrument (WHOQOl-Bref). To comply with the ethical aspects of resolution 466/2012, the research was approved by the ethics and research committee involving human beings under the number of CAAE: 63798217.6.0000.5186. RESULT: Through the analyzes, it was noticed a homogeneity between the groups regarding the socio demographic variables, food insecurity, quality of life and anxiety. Therefore, the analysis was performed with the joining of the two groups. Through this, a relationship was observed between the FI variables, QL Anxiety, so, when the FI increases, anxiety also increases and the women's QL decrease, causing a relation of cause-effect between the variables. FINAL CONSIDERATIONS: There is a relation between food insecurity, anxiety and quality of life. So, that increased anxiety and decreased quality of life is an effect of increased anxiety.